Can trade contribute to a global environmental sustainability? - Elverdin, Pablo; Glauber, Joseph W.; Laborde Debucquet, David; Piñeiro, Valeria (International Food Policy Research Institute, 2022)
Achieving world food security is more complex nowadays. It is not only necessary to pay attention to the availability of food, but also to the way in which it is produced, paying special attention to the impact of the food production systems on climate change and natural resources sustainability. The challenge is to produce a diversified basket of nutritious food in sufficient quantity while reducing greenhouse gas emissions and minimizing the impact on natural resources. Accomplishing these diverse goals requires an integrated strategy that takes into account increased productivity and the environmental sustainability of food production systems with a focus on efficient use of land, water, fertilizers and energy.